Stabilization of Expansive Soils with Lime and Fly Ash - Kamal Singh (Stabilization of Expansive Soils with Lime and Fly Ash, 2023)
The expansive soils, popularly known as Black cotton soils in India are very problematic as they are poor material for foundation as well was construction. Structures resting on expansive soils are subjected severe distress due to ground movement caused by the swelling and shrinkage of soils. Normally the types of foundations vary depending upon the availability of soil strata as well as cost involvement. Some times, it is essential to build a heavy structure over a weak soil, in such situation improvement of bearing capacity of soil by some suitable methods becomes necessary. The techniques generally adopted are stabilization and reinforcement of the soil. The stabilization of soil by admixing some stabilizing agent has an effective ground improvement because of its easy adoptability and cost effectiveness. If the admixing material is available in abundance at free of cost, it will reduce construction cost. Mixing of lime is one of the methods to stabilize the expansive soils. With mixing of lime, the properties like swelling/shrinkage get reduced and some engineering properties are improved. Fly ash, an industrial waste of thermal power plants has many geotechnical uses. The case study is on stabilization stabilization of expansive soils with lime and fly ash is presented. The behavior of soil has been studied using different percentage of fly ash with the combination of lime. From the case study results it is found that engineering properties of expansive soil improves with the addition of lime and fly ash. Swelling and shrinkage is effectively reduced. With the addition of fly ash, the same results can be obtained at lower percentage of lime.